Burundi Education : Summary of the Findings of the Four Analytical Studies - World Bank (Washington, DC, 2017)
The World Bank is re-engaging in the education sector in Burundi at a time when the country has launched a major reform of its school education system, including the lengthening of the compulsory basic education cycle to 9 years in line with the Sustainable Development Goals. Due to the withdrawal of many donors from the education sector, after the events of 2015, as well as the general fiscal and economic contraction, the gains achieved in the last decade, especially in primary education, might be rapidly eroded. Consequently, a stock-taking exercise was undertaken by the Bank, focusing on four areas identified at the time of the concept note review. This summary report is based on the four pieces of analytical work and is intended to help the World Bank engage with all stakeholders in order to consolidate the recent gains and move the reform forward. In the next fiscal year, the findings from these studies will be used to engage in a broader dialogue and consensus building with the key stakeholders.